Implications of Compulsory Car Accident Insurance Comparative Study - et. al., Nadia Yas , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Compulsory civil liability insurance on car accidents is one of the most important topics, which aims to achieve traffic safety and reduce car accidents. Today, car accidents constitute a great danger to human life as they cause different types of physical and moral damages. This study, however, attempts to highlight the effectiveness of compulsory insurance in providing legal protection for damages resulting from car accidents. Such protection can be achieved through the process of creating legal mechanism to enable injured people to refer to insurance companies. It is quite apparent that nobody can deny the importance of insurance and its influence on people’s lives. Insurance companies nowadays have become an essential cornerstone in the economy of any country. An insurance contract has legal consequences on the parties, which leads to corresponding obligations. These parties are committed to comply with these obligations otherwise, any violation will be treated as per the prescribed legal sanctions. In conclusion, any research or study on the compulsory insurance system whether in the Emirati law or in Islamic Sharia is highly recommended as part of the attempts to solve and rectify any legal and legitimate problems in this system. An essential objective of the Islamic Sharia is to achieve all fair interests of people. Arab and international legislation consider car insurance compulsory with some exceptions in order to compensate all those affected by a car accident. Arab and other foreign laws as well as the legitimate ones have differed in their choices of car insurance basis. Many legislations in the field of compulsory insurance have limited the right of compensation to body damage. Some other legislations have covered damages of property. Most legislations have not specified the amount of compensation that the insurer is obliged to pay in case of injury, death, or property damages. companies.